The relationship between organizational structure, organizational agility and information and communication technology - Omrani, Mohammad; Zarei, Reza (Opción, 2019)
The purpose of this study was to examine the mediatory role of ICT1 in the relationship between organizational structure and organizational agility. The method was descriptive with correlational design. The population was all workers of the Methanol Company of Deir. Since the population was limited, sampling was redundant and the whole population selected as a sample by census. The results of the study showed that organizational structure has a direct and significant relationship with ICT. Organizational structure and ICT have a direct relationship with organizational agility